The Urgency of Indonesian Islamic Fashionpreneur as Part of The World's Halal Industry - Indriya Indriya; Reza Maulana; Alfain Baihaqi; Vedo Vikanda; Ardi Ramadhan (Universitas Muhammadiyah Jakarta, 2021)
Indonesia is a country that has great potential to become the center of the world's halal industry. This is analogous to the largest Muslim population, and Indonesia is ranked fourth in the development of the sharia economy. On the other hand, this is also analogous to people's consumption patterns for clothing or fashion needs that are always evolving, and become part of human secondary needs. That way, we can maximize efforts to make Indonesia the center of the halal industry in the world, especially in the field of Islamic fashionpreneur. Currently, there are many Muslim fashion start-ups and Muslim fashion designers born in Indonesia. This is in line with human desire for an elegant style to beautify their appearance and increase their self-confidence. Based on the data and the reality on the ground, Indonesia has a huge opportunity to become the center of the world's halal industry through Islamic Fashionpreneur. Obstacles in Indonesia's development to become the center of the world's halal industry through Islamic Fashionpreneur, among which are raw materials that are difficult to obtain or cannot be provided domestically or still have to be purchased or imported from other countries. Besides, on average, most Muslim fashion craftsmen still use traditional technology and can be said to be